A Work Environment Blind Spot – Exploring School Principals’ Organisational and Social Work Environments - Edvik, Anders; Muhonen, Tuija (Scandinavian Journal of Public Administration, 2022)
This article examines principals’ social work environment in the context of a series of school reforms inspired by new public management. With the point of departure in Job Demands and Resources, we put forward the following overall research question: which job demands and job resources are related to principals’ job satisfaction? The article has a mixed methods approach, combining material from questionnaires (466 participants) and interviews (15 participants). The results of the questionnaire indicate that job resources such as role clarity, influence, meaningfulness, and social community with senior managers were related to job satisfaction, while lacking job resources (influence, social community with senior managers) and experiencing role conflicts were associated with a higher intention to leave the profession. The interviews provide a more in-depth understanding of the shift of institutional logics within the school sector, enforcing boundaries between principals’ professional and managerial roles in accordance with New Public Managerial Ideas. The separation between profession and management contributes to principals’ organisational and social work environments being in a blind spot. This is not only a problem for the principals, but also a risk factor for the organisations themselves, as stress and ill-health among leaders tend to affect the entire organisation.